Phytochemicals and therapeutic potentials of Barleria lupulina - Hemant Arunrao Sawarkar; Ajit Kumar Pandey; Kailas R. Biyani (Bangladesh Pharmacological Society, 2023)
A well-known herb Barleria lupulina is traditionally used as a medicinal and decorative plant. The various parts of this plant are reported to contain a range of phytoconstituents, including terpenes and terpenoidal compounds, iridoid glucosides, iridoid diglucosides, phenylpropanoid glucosides, and phenylethanoid glucosides. Antibacterial, antiarthritic, CNS depressive, anti-osteoporotic, antioxidant, anti-diabetic, and anti-inflammatory effects are present in isolated components and extract of B. lupulina. This in-depth analysis covers the traditional uses, phytochemistry, pharmacological use, and mechanism of action of B. lupulina.